Konstruksi Makna Dimensi Nilai Ilahiyah Dan Nilai Insaniyah Dalam Film “Atas Nama Surga”: Analisis Semiotika - Putri Bunga Yossilia; Fafi Inayatillah (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
In the modern era, film has become a communication medium that is not only a means of entertainment, but also a space for constructing meaning that represents values ​​in life, including religious values. Research on religious values ​​in films generally still focuses on introducing religious messages without examining how these values ​​are constructed through a complete sign system. Therefore, this study aims to describe the representation of the dimensions of divine and human values ​​contained in the film "Atas Nama Surga" through Charles Sanders Peirce's semiotic analysis. A qualitative-descriptive method is used in this study with data in the form of visual scenes and dialogues that represent these two dimensions of value. Data collection was carried out by observing and taking notes through the stages of observation (watching the film repeatedly), noting scenes relevant to the research topic, interpreting the data by analyzing the relationship between the triangle of signs (representamen, objects, and interpretants) according to Charles's semiotic theory, and continued with documentation and drawing conclusions. The results of the study show that the representation of these values ​​is constructed through complementary visual and verbal signs. The dimensions of divine values ​​are represented through: 1) worship as a spiritual response to life's trials; 2) prayer as a form of asking for help from Allah SWT. The world is included in the dimension of worship as a form of approaching Allah SWT. Meanwhile, the human dimension is represented through morals in the form of: 1) helping each other as a form of caring for sesame; 2) loyalty as a form of commitment to maintaining the integrity of the household. This research is expected to contribute to the development of semiotics and become a reference for further research that examines religious values ​​in films.